Lactogenic effects of tannin and aglycone form of aqueous extract (AFAE) from Musa x paradisiaca flower on lactating rats - Azizah Mahmood,; Noor Salihah,; Muhammad Nor Omar,; Nurziana Ngah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research is aimed to investigate the in vivo lactogenic effects of Musa x paradisiaca flower extracts, namely the aglycone form of aqueous extract (AFEA) and condensed tannin (CT) on lactating rats. Lactating rats (n=6) of Spraque Dawley with six pups each were orally administered with aqueous extract, AFEA, CT and metoclopramide. They were daily administered starting Day 5 until Day 14 and the performance was measured by weight-suckle-weight method. Results were analysed using SPSS by means of ANOVA at 0.05 and was expressed as their mean ± standard deviation. Milk production of rats treated with AFAE (4.65 ± 1.67 gm/pup/day) and aqueous extract (4.86 ± 2.36 gm/pup/day) were comparable with each other and significantly higher than negative control (3.63 ± 2.10 gm/pup/day) group. The groups treated with aqueous, AFAE, metoclopramide and CT were observed to increase milk yield by 28.03%, 24.87%, 2.63% and 2.20%, respectively, compared to negative control. The percentage body weight increment of pups for aqueous extract, AFAE, negative control, metoclopramide and CT, respectively were 148.21%, 122.29%, 113.8%, 101.53% and 87.06%. This research reveals the potential efficacy of bioactive compounds from Musa x paradisiaca flower to enhance milk production of inadequate supply of milk for breastfeeding mothers.